COMPARISON OF PLANTING SHRUB PEPPER (Piper nigrum L.) FLOATING AND DRY LAND WITH MAGNESIUM FERTILIZER TREATMENT (Mg) - Kartika Putri; Momon Sodik Imanuddin; Bakri Bakri (BIOVALENTIA: Biological Research Journal, 2023)
The cultivation of pepper plants is usually carried out on dry land, but at this time there is a lot of conversion of pepper plantations to other plantations and even housing. This study aimed to investigate the growth ratio of floating agricultural pepper and dry land, study the best Mg dosage for the growth of pepper with float-ing and dry land systems, andinvestigate the planting system on soil moisture content, pH and Mg content of soil and plants. The research was carried out from September 2020 to January 2021 in the gardens of the Soil Department, Faculty of Agriculture, Sriwijaya University, Indralaya. This research was conducted using the Split Plot Design method with 2 factors. As the main plot is the farming system, namely: S1 = Floating. S2 = On dry land (conventional). Subplots were Mg fertilizer with doses per polybag: Mg0 = No Mg fertilizer, Mg1 = 4g plant-1 , Mg2 = 8 g plant-1 , Mg3 = 12 g plant-1 , Mg4 = 16 g plant-1 . Observations were made on the increase in plant height, number of leaves, elemental content mg, soil water content, soil pH. The results showed that the planting system had an effect on plant height, number of leaves in the 11th week and root length, Mg doses did not affect the growth of pepper and soil. The soil water content of the floating system is higher than the conventional system, whereas the pH is higher in the conventional system than the floating system.